FUNDAMENTAL ISSUES OF PURULENT MEDIASTINITIS - Boboyev, Q.Kh.; Babokhodjaev , A.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
This review article presents information on the pathological anatomy of purulent mediastinitis, on the specificity of the pathogenesis of purulent mediastinitis, in particular the local process and the mechanisms of development of its complications. Modern information about the system of general and anti-infective resistance of the organism in the development of purulent mediastinitis is described in detail. It is concluded that purulent mediastinitis is a severe pathological process affecting vital organs and leading to the development of multiple organ dysfunction or insufficiency. It is lesions of this nature that act as the basis for the development of severe sepsis and septic shock, leading to death.